Leczenie odwarstwienia siatkówki w przebiegu retinopatii wcześniaków - Prost, Marek E. (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Cryo- and laser therapy of stage 3 have reduced, but not eliminated the occurrence of retinal detachment in stages 4a, 4b and 5 of ROP. In this disease the treatment of these stages is still the greatest challenge to the ophthalmologist. Therefore, the aim of this paper is to present our up-to-date possibilities of treatment of different kinds of retinal detachments in ROP, including segmental scleral buckling, encircling scleral buckling, scleral resection, vitrectomy and its modifications in ROP. Guidelines of surgery of retinal detachment in active stages 4 and 5 of retinopathy of prematurity have been described.